Adenotonsillar Hypertrophy as a Cause of Failure to Thrive - Ann G Sheehan; R Brent Scott; Helen M Machida (Canadian Journal of Gastroenterology)
Two infant aged 11 and 15 months presented to the Gastroenterology Clinic at Alberta Children's Hospital because of failure to thrive. Clinical and laboratory investigations excluded any underlying abnormality of 1he gastrointestinal tract. Because of a history of obstructive upper respiratory symptoms, both were referred for ear, nose and throat evaluation, and both were found to have partial upper airway obstruction secondary to adenotonsillar hypertrophy. Subsequent adenotonsillectomy led to resolution of obstructive upper respiratory symptoms and dramatic increases in weight gain and growth. Adenotonsillar hypertrophy should be included among the potential causes of failure to thrive in infancy, especially if the child has a history of obstructive upper respiratory symptoms.